Preliminary study on diffusion welding of marine grades grey cast iron to low carbon steel - Ayob, F.B. (Asian Research Publishing Network, 2017)
Experimental research on joining of grey lamellar graphite cast iron to low carbon steel specimens is being performed under various diffusion welding parameters and variables to examine the effects on their microstructural and mechanical properties. Optimum conditions that produce excellent welding characteristics shall be established, the diffusion process mechanisms observed, the inter-diffusion coefficients and the activation energy of the diffusion system investigated. One of the expected outcomes from this research is to establish the methodology to produce the ultimate weldability of cast iron to steel. This paper updates the progress of this research; the research started with the preparation of the materials and the equipment involved. Base materials used were verified against the inspection/mill certificates by conducting microstructural, compositional and basic mechanical testing. Preliminary studies on diffusion welding experiments were conducted on a few specimens of the materials involved. Although initial few specimens failed to produce credible joints, further investigations on equipment unique characteristics led to making the right adjustments on the parameters and procedures that finally produced good joints on subsequent experiments.